2021
DOI: 10.1021/acscatal.1c00331
|View full text |Cite
|
Sign up to set email alerts
|

Coke Deposition on Pt-Based Catalysts in Propane Direct Dehydrogenation: Kinetics, Suppression, and Elimination

Abstract: Pt-based catalysts are widely used in propane dehydrogenation to meet the dramatically increased demand of propylene from an on-purpose catalytic process. Although the process has been commercialized with high selectivity for decades, the prevention of coke deposition is still a daunting challenge. Herein, in order to provide a full coverage of the impact of coke deposition, we critically analyze the process of coke formation on Pt-based catalyst. First, the intrinsic nature of coke, including composition, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 114 publications
6
55
0
Order By: Relevance
“…[30] In addition to Pt, [1,31] Au [32][33] and Ru [34][35] are also popular singleatom systems. When combined with a thermally stable support such as h-BN, these SACs may offer attractive advantages for dehydrogenation of propane, especially in anti-coking and in improving the turnover frequency per Pt atom, as coke formation [36] is a known problem for the conventional Pt/ alumina catalyst where Pt exists as nanoclusters of 15-25 atoms. [25] Answering these questions computationally can help guide the experimental discovery of h-BN-supported single atoms for PDH.…”
Section: Introductionmentioning
confidence: 99%
“…[30] In addition to Pt, [1,31] Au [32][33] and Ru [34][35] are also popular singleatom systems. When combined with a thermally stable support such as h-BN, these SACs may offer attractive advantages for dehydrogenation of propane, especially in anti-coking and in improving the turnover frequency per Pt atom, as coke formation [36] is a known problem for the conventional Pt/ alumina catalyst where Pt exists as nanoclusters of 15-25 atoms. [25] Answering these questions computationally can help guide the experimental discovery of h-BN-supported single atoms for PDH.…”
Section: Introductionmentioning
confidence: 99%
“…The exact composition of the coke is, to date, the subject of study. It has been suggested that the coke formed on PtSn-based catalysts in PDH reaction mainly consists of three kinds of species: aliphatics, aromatics and pregraphite, with the aliphatic one constituting most of the deposit, with the C/H ratio of around 1.5 [95]. Raman studies on exhausted Pt-Sn/SBA-16 catalysts have shown an increase in coke crystal size from 60 to 180 min on stream and from 180 to 300 min under reaction [96].…”
Section: Catalyst Regeneration and Coke Combustion Kineticsmentioning
confidence: 99%
“…The cofeeding of hydrogen decreases the coke formation rate and increases the stability of the catalyst by removing the precursor of coke, while the cofeeding of water decreases the coke formation while increasing the activity by decreasing the apparent activation energy of propane conversion [95].…”
Section: Catalyst Regeneration and Coke Combustion Kineticsmentioning
confidence: 99%
“…The quasi steady-state assumption results from the significant higher reaction rates R 1 -R 5 (Equations ( 1)-( 5)) in comparison to the overall coke formation rate (Equation (18)). The squared difference between the experimental and simulated values is minimized for the parameter estimation by the objective function:…”
Section: Activity-time Relationshipmentioning
confidence: 99%
“…Thus, a periodic catalyst regeneration is necessary, reducing space-time yield and productivity. To avoid coke formation, various approaches are studied, such as the co-feed of hydrogen and steam, the structure and size of the active catalyst component, the effect of the catalyst promoter and the modification of the catalyst support [18]. In this contribution, the focus lays on the exothermic (ΔH R 0 = -118 kJ/mol) oxidative propane dehydrogenation with oxygen (ODH), since present oxygen depresses coking.…”
Section: Introductionmentioning
confidence: 99%